2017
DOI: 10.1093/imrn/rnw320
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity of Compact Pseudo-Riemannian Homogeneous Spaces for Solvable Lie Groups

Abstract: Let M be a compact connected pseudo-Riemannian manifold on which a solvable connected Lie group G of isometries acts transitively. We show that G acts almost freely on M and that the metric on M is induced by a bi-invariant pseudo-Riemannian metric on G. Furthermore, we show that the identity component of the isometry group of M coincides with G.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In favorable cases, nil‐invariance of ·,· already implies invariance. For solvable Lie algebras frakturg, this is always the case, as was first shown in . These results are briefly summarized in Section 4.…”
Section: Introduction and Main Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…In favorable cases, nil‐invariance of ·,· already implies invariance. For solvable Lie algebras frakturg, this is always the case, as was first shown in . These results are briefly summarized in Section 4.…”
Section: Introduction and Main Resultsmentioning
confidence: 62%
“…Pseudo‐Riemannian homogeneous spaces of arbitrary index were studied by Baues and Globke for solvable Lie groups G. They found that, for solvable G, the finite volume condition implies that the stabilizer H is a lattice in G and that the metric on M is induced by a bi‐invariant metric on G.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations